3D Printing: 3D Printing of Highly Stretchable and Tough Hydrogels into Complex, Cellularized Structures (Adv. Mater. 27/2015). (July 2015) - Hong, Sungmin; Sycks, Dalton; Chan, Hon Fai; Lin, Shaoting; Lopez, Gabriel P.; Guilak, Farshid; Leong, Kam W.; Zhao, Xuanhe
<x xml:space="preserve">Abstract</x> X. Zhao and co‐workers develop on page 4035 a new biocompatible hydrogel system that is extremely tough and stretchable and can be 3D printed into complex structures, such as the multilayer mesh shown. Cells encapsulated in the tough and printable hydrogel maintain high viability. 3D‐printed structures of the tough hydrogel can sustain high mechanical loads and deformations.